Upaya Budidaya Jamur Tiram Putih Bagi Penggerak Ekowisata Kampung Rhepang Muaif, Distrik Nimbokrang Kabupaten Jayapura - Evan C.B. Kainama; Silva D. Febrianty; Gemala D. Dirgantari; Graziani S.S. Rumbino; Carolus M. Raya; Mega E.K. Linggi; Florence A. Manuhutu; Aprillia T. Masduky; Jessy K. Matuan; Enjelrika P. Simolinggi; Sonia K. Kwano; Diana Abulais; Euniche R.P.F. Ramandey (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Cultivation of white oyster mushrooms (Pleurotus ostreatus) can be solution of strengthening food security during pandemic Covidâ€“19. However, the procedure for cultivating white oyster mushrooms (P. ostreatus) is unknown due because the limited knowledge, so the purpose of this activity is to provide learning to the community about white oyster mushroom cultivation for the Isyo Hills Birdwatching ecotourism group at Rhepang Muaif Village, Nimbokrang District, Jayapura Regency. The results of the activity showed an increase in public interest in cultivating white oyster mushrooms. As many as 73% of the people of Kampung Repang know that mushrooms can be processed into nutritious food ingredients, even 60% of the people of Kampung Rhepang have processed or cooked mushrooms with a variety of dishes. However, there are 73% of people who have never seen the process of cultivating white oyster mushrooms, therefore there are 93% of people interested in cultivating white oyster mushrooms.Â Keyword: cultivation; oyster mushroom; Rhepang Muaif; Jayapura.